|x²-x-6|/(x²-x-6)>|-x²+9x-14|/(x²-9x+14) x²-x-6=0 D=1+24=25>0⇒x1+x2=1 U x1*x2=-6⇒x=-2 U x=3 x²-9x+14=0⇒D=81-56=25>0⇒x1+x2=9 U x1*x2=14⇒x1=2 U x2=7 + _ _ + + (x²-x-6) (-2)(2)(3)(7) _ _ + + _ (-x²+9x-14) 1)x<-2 (x²-x-6)/(x²-x-6)>(x²-9x+14)/(x²-9x+14) 1>1 нет решения 2)-2<x<2 -(x²-x-6)/(x²-x-6)>(x²-9x+14)/(x²-9x+14) -1>1 нет решения 3)2<x<3 -(x²-x-6)/(x²-x-6)>-(x²-9x+14)/(x²-9x+14) -1>-1 нет решения 4)3<x<7 (x²-x-6)/(x²-x-6)>-(x²-9x+14)/(x²-9x+14) 1>-1 x∈(3;7) 4)x>7 (x²-x-6)/(x²-x-6)>(x²-9x+14)/(x²-9x+14) 1>1нет решения ответ x∈(3;7)
НЕТ, ЭТО НЕ СЛИШКОМ КОРОТКО, СПРАЩИВАЙ,РУ